2014 IEEE 26th International Symposium on Power Semiconductor Devices &Amp; IC's (ISPSD) 2014
DOI: 10.1109/ispsd.2014.6856027
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the dynamic characteristics of Au-free AlGaN/GaN Schottky Diodes on 200 mm Si wafers by surface treatments

Abstract: Abstract-In this work we show the impact of surface cleaning on the dynamic characteristics of Au-free AlGaN/GaN Gated Edge Termination Schottky Barrier Diodes (GET-SBDs). It is demonstrated that the current dispersion (measured in pulsed regime) can be reduced by introducing a N 2 plasma cleaning step in the anode metal deposition chamber. Moreover, diodes treated with N 2 plasma show lower current drop after reverse voltage stress (with a relative forward voltage increase of 2% after stress) than diodes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A N 2 plasma treatment was given to remove the native oxide or traps located at the AlGaN surface before the deposition of anode metal. 24) The anode metal stack consists of 20 nm TiN=20 nm Ti=250 nm Al=20 nm Ti=60 nm TiN. A Au-free metal stack of 5 nm Ti= 100 nm Al=20 nm Ti=60 nm TiN was used for the cathode contact formation, which was annealed at a low temperature of 550 °C.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A N 2 plasma treatment was given to remove the native oxide or traps located at the AlGaN surface before the deposition of anode metal. 24) The anode metal stack consists of 20 nm TiN=20 nm Ti=250 nm Al=20 nm Ti=60 nm TiN. A Au-free metal stack of 5 nm Ti= 100 nm Al=20 nm Ti=60 nm TiN was used for the cathode contact formation, which was annealed at a low temperature of 550 °C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Meneghini et al 23) have reported a permanent degradation mechanism of vertical AlGaN=GaN Schottky diodes on Si. Lenci et al 24) presented that electron trapping under the Schottky metal can result in SBD dispersion from dynamic characterization, thus AlGaN surface cleaning was proposed for the improvement in performance. 25,26) Hu et al 16) showed and explained the phenomenon of total current collapse of lateral AlGaN=GaN SBDs [in pulsed current-voltage (I-V) measurements] due to electron-trapping and Fermi-level pinning at the AlGaN= Si 3 N 4 interface near the Schottky contact corner.…”
Section: Introductionmentioning
confidence: 99%